Influencer marketing strategies for enhancing brand equity: The role of brand awareness and customer engagement on Le Secre Parfume - Purbasari, Angelica; Lasmy, Lasmy (Edelweiss Applied Science and Technology, 2025)
This study primarily aims to investigate how influencer marketing affects brand awareness, overall brand equity, and customer brand engagement, and further explores its influence on overall brand attachment when moderated by brand awareness and customer brand engagement. Employing a purposive sampling method, the research collected data from 200 respondents. The analysis was conducted using Structural Equation Modeling (SEM) with the AMOS software to examine the complex relationships between the variables. The findings reveal that influencer marketing positively impacts brand awareness, overall brand equity, and customer brand engagement. Moreover, influencer marketing also has a significant positive effect on overall brand attachment, with brand awareness and customer brand engagement serving as moderating variables in this relationship.